Adsorption and diffusion on nanoclusters of C-60 molecules - Baletto, F; Doye, J; Ferrando, R; Mottet, C (2003)
The adsorption and the energy barriers for diffusion on clusters of C60 molecules are studied by means of quenched molecular dynamics simulations. The interaction among the C60 molecules is modeled by means of the Girifalco potential. Three different clusters structures are considered: a truncated octahedron of 38 molecules, an icosahedron of 55 molecules and a truncated decahedron of 75 molecules. © 2003 Elsevier Science B.V. All rights reserved.